The dynamic relationship of sentence complexity, childhood stuttering, and grammatical development - Bauerly, Kimberly R (ProQuest Dissertations & Theses, 2007)
The present study was conducted to determine if the relationship between grammatical complexity and childhood stuttering is influenced by grammatical development. The study was cross-sectional in design and observed the spontaneous speech of six children who stutter ranging in age from 32 to 46 months. The first 100 utterances from each subject's sample were scored using Scarborough's (1990) Index of Productive Syntax (IPSyn) and given a numerical score which was used as an indicator of grammatical development in place of the child's age. The first one-hundred sentences containing a noun and verb in subject-predicate relationship were extracted from each sample and coded for their grammatical complexity using Lee's (1973) Developmental Sentence Score. The utterances were also measured for the length in morphemes. Sample utterances were then separated into two categories: fluent and stuttered. Results showed that when conducting group comparisons the mean complexity levels of fluent and stuttered utterances were significantly different. The difference in complexity levels of the fluent and stuttered utterances, however, was not found to be significant when the length of the utterance was held constant. To determine if the difference in sentence complexity of fluent and stuttered utterances was related to age and/or IPSyn, bivariate correlation analyses were conducted. Results showed that the differences between the mean complexity levels of the fluent and stuttered utterances were not significantly correlated with grammatical development. However, an apparent correlation was observed when depicted in graph form. It was found that the difference in complexity of fluent and stuttered utterances became more apparent as a child increased in grammatical development. Findings suggest that as a child's grammatical repertoire expands, simpler sentence forms are fluent while the newly acquired sentence forms are dysfluent. Findings suggest that the incidence of stuttering shifts along a developmental continuum, occurring more often on the child's emerging grammar forms.